939. Predicting Attributable Mortality in Pediatric Patients with Cancer Admitted to the Intensive Care Unit for Suspected Infection. (4th December 2021) - Rubnitz, Zach; Agulnik, Asya; Merritt, Pamela; Ferrolino, Jose Amadeo A; Dallas, Ronald; Tang, Li; Sun, Yilun; Allison, Kim J; Wolf, Joshua; Wolf, Joshua
Abstract: Background: Infection and sepsis are important contributors to mortality in children with cancer. Although pediatric risk prediction scores have improved identification of children at high risk of death in the PICU, the value of these tests in immunocompromised children is unknown. Methods: In this IRB-approved retrospective study performed at St. Jude Children's Research Hospital, we evaluated the performance of 4 pediatric risk scores, the Pediatric Risk of Mortality (PRISM), Pediatric Sequential Organ Failure Assessment (pSOFA), Quick Sequential Organ Failure Assessment (qSOFA) scores (using data available at 1, 6, 12 and 24 hours) and the Paediatric Index of Mortality 3 (PIM-3) score (at 1 hour), to predict attributable mortality (death ≤ 60 days without organ dysfunction recovery). Inclusion criteria: Age < 24 years, active cancer therapy (other than bone marrow transplantation), and admission to PICU between 2013 and 2019 with suspected infection (collection of a blood culture and initiation of antibiotic therapy). Scores were calculated using the worst value obtained for each variable. Score distributions were compared by the Mann-Whitney U test, and optimal cutoffs selected by maximizing Youden's index. An unadjusted p-value < 0.05 was considered statistically significant. Results: Of 202 episodes of PICU admission for suspected infection in 168 participants, there were 12 attributable (6%) and 4 unrelated (2%) deaths. Demographic and cancer-related characteristics were not associated with mortality (Table 1). Of the 4 prediction scores, only the PRISM score at 24 hours was associated with mortality (P = 0.012; Table 2). For PRISM score ≥ 18, sensitivity was 58.3%, specificity was 81.6%, positive predictive value was 16.7%, and negative predictive value was 96.9% for attributable mortality. Table 1. Risk factors for attributable mortality in pediatric patients with cancer admitted to the intensive care unit with suspected infection. Table 2. Association between risk prediction scores and attributable mortality in pediatric patients with cancer admitted to the intensive care unit with suspected infection. Conclusion: In children with cancer admitted to PICU with suspected infection, early pediatric risk prediction scores did not predict mortality. The PRISM score calculated at 24 hours did predict mortality but was relatively insensitive. Further research is needed to develop a risk score for immunocompromised children and to validate the 24 hour PRISM score in this population. Disclosures: Joshua Wolf, MBBS, PhD, FRACP, Karius Inc. (Research Grant or Support) Joshua Wolf, MBBS, PhD, FRACP, Nothing to disclose